2016
DOI: 10.3390/diagnostics6040041
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid as a Novel Potential Source of Biomarkers Distinguishes Pubertal from Post-Pubertal Subjects

Abstract: Detection of pubertal growth peak is vital in orthodontic treatment timing and planning. Gingival crevicular fluid (GCF) contains abundant proteins from different sources and has been proven to be an ideal source of biomarkers. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) is an advanced technique that can detect low-molecular-weight peptides with high sensitivity and resolution. The aim of this research was to identify novel candidate biomarkers in GCF to help the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Generally, the peptide profiling investigations that we summarize in this review make use of surface enhanced laser desorption ionization (SELDI) [17,18] and matrix-assisted laser desorption ionization (MALDI)-MS [6,[19][20][21][22][23][24][25][26] approaches which result more suitable and easily applicable for the analysis of natural peptides of GCF (Table 1). However, few investigations based on electrospray ionization (ESI)-MS have also been carried out to explore peptidic components and small proteins found in GCF in a top-down fashion [27][28][29] (Table 1).…”
Section: Low Molecular Weight Profiling Of Gcfmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the peptide profiling investigations that we summarize in this review make use of surface enhanced laser desorption ionization (SELDI) [17,18] and matrix-assisted laser desorption ionization (MALDI)-MS [6,[19][20][21][22][23][24][25][26] approaches which result more suitable and easily applicable for the analysis of natural peptides of GCF (Table 1). However, few investigations based on electrospray ionization (ESI)-MS have also been carried out to explore peptidic components and small proteins found in GCF in a top-down fashion [27][28][29] (Table 1).…”
Section: Low Molecular Weight Profiling Of Gcfmentioning
confidence: 99%
“…Peptidomics workflow, without a digestion step, allows to preserve the endogenous information of peptides from GCF, including post-translational modifications and proteolytic products. (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Fibrinopeptide B Generally, the peptide profiling investigations that we summarize in this review make use of surface enhanced laser desorption ionization (SELDI) [17,18] and matrix-assisted laser desorption ionization (MALDI)-MS [6,[19][20][21][22][23][24][25][26] approaches which result more suitable and easily applicable for the analysis of natural peptides of GCF (Table 1). However, few investigations based on electrospray ionization (ESI)-MS have also been carried out to explore peptidic components and small proteins found in GCF in a top-down fashion [27][28][29]…”
Section: Low Molecular Weight Profiling Of Gcfmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, any method that is noninvasive with minimum side effects and that can help the clinician to identify the growth spurt is in highly demand. Research that showed variable peptides in the GCF of both pre-pubertal and post-pubertal subjects has been conducted recently [ 28 ]. Further studies are encouraged to find more information about these novel biomarkers.…”
Section: Gcf As a Diagnostic Tool For Analysis Of Oral Diseasesmentioning
confidence: 99%